Chromium-Related Degradation of Thin-Film Electrolyte Solid Oxide Fuel Cell Stacks. Issue 12 (20th August 2015) - Menzler, Norbert H.; Sebold, Doris; Fang, Qingping
Abstract : SOFC short stacks with thin-film electrolyte anode-supported cells were operated for up to ∼3, 000 h and post-test characterized. The cells consisted of thin electrolyte films (≤ 3 μm) and LSCF or LSC cathodes. Typical manganese-oxide chromium evaporation protection layers and perovskitic cathode contact layers were used. Operating parameters were: temperatures between 600°C and 750°C, a current density of 500 mA/cm², hydrogen with 20% water vapor as fuel, and a fuel utilization of ∼40%. Microstructural characterization revealed that Cr-containing phases formed at different locations. SEM and TEM analysis of some cells additionally showed microstructural changes within the GDC layer. A possible explanation for the different chromium-containing phase locations based on theoretical assumptions is given.